Implementation of patient-centred care: which organisational determinants matter from decision maker’s perspective? Results from a qualitative interview study across various health and social care organisations - Lena Ansmann; Holger Pfaff; Kira Isabel Hower; Vera Vennedey; Hendrik Ansgar Hillen; Ludwig Kuntz; Stephanie Stock (BMJ Open)
Objectives Health and social care systems, organisations and providers are under pressure to organise care around patients’ needs with constrained resources. To implement patient-centred care (PCC) successfully, barriers must be addressed. Up to now, there has been a lack of comprehensive investigations on possible determinants of PCC across various health and social care organisations (HSCOs). Our qualitative study examines determinants of PCC implementation from decision makers’ perspectives across diverse HSCOs.Design Qualitative study of n=24 participants in n=20 semistructured face-to-face interviews conducted from August 2017 to May 2018.Setting and participants Decision makers were recruited from multiple HSCOs in the region of the city of Cologne, Germany, based on a maximum variation sampling strategy varying by HSCOs types.Outcomes The qualitative interviews were analysed using an inductive and deductive approach according to qualitative content analysis. The Consolidated Framework for Implementation Research was used to conceptualise determinants of PCC.Results Decision makers identified similar determinants facilitating or obstructing the implementation of PCC in their organisational contexts. Several determinants at the HSCO’s inner setting and the individual level (eg, communication among staff and well-being of employees) were identified as crucial to overcome constrained financial, human and material resources in order to deliver PCC.Conclusions The results can help to foster the implementation of PCC in various HSCOs contexts. We identified possible starting points for initiating the tailoring of interventions and implementation strategies and the redesign of HSCOs towards more patient-centredness.Trial registration number DRKS00011925.